Perbedaan Padat Penebaran Terhadap Kualitas Air Ikan Nila Merah (Oreochormis sp) Pada Sistem Budikdamber - Vina Nur Nadiro; Sri Andayani; Maheno Sri Widodo; Nurhalisa Nurhalisa (Jurnal Penelitian Pendidikan IPA, 2023)
The problems of fish and plant cultivation are limited land, decreasing quality and quantity of water for human needs, food sources, and increasing population on earth. Optimization of fish farming with high stocking densities accompanied by high feeding will cause accumulation of organic matter in the culture containers which will worsen the quality of the rearing water which will ultimately have an impact on the physiological conditions, survival and growth of fish. One of the technologies for growing vegetables, fruit and fish farming that has been developed to overcome these obstacles is the Budikdamber system with red tilapia organisms and water spinach plants. The purpose of this study was to determine the quality of water with different stocking densities in the Budikdamber system with water spinach and without water spinach. The experimental design used a factorial complete randomized design with density treatment (A (2 fish/10L), B (4 fish/10L), C (6 fish/10L), D(8 fish/10L) and system (budikdamber with water spinach) (a) and without water spinach (b)). The results showed that temperature parameters ranged from 22.4 - 30.6°C, pH ranged from 6.4 - 8.9, and DO ranged from 1.07 - 16.4 mg/l. Parameters of temperature, pH, and DO are in a range that is not in accordance with optimum conditions (temperature = 25-32°C, pH = 6.5 – 8, and DO ≥3 ), but can still be tolerated by tilapia so that fish tilapia still survive. Water spinach plants can reduce ammonia so that the ammonia value in the treatment using kale decreased from week 1 to 4 and conversely, for budikdamber without water spinach, it increased from week 1 to week 4. The highest SR value was found in the Ba treatment (4 fish/10 liters) with water spinach is 91.67%.